The Policies of Islamic Religious Education in Schools and Universities (Correlation between Problems and Solutions) - Afandi, Rahman (International Conference of Moslem Society, 2018)
Educational issues are never ending issues to be discussed because these issues concern on the matter of humans in giving the meaning and the direction to their existence. Education is a guidance conciously conducted by the educators toward physical and spiritual developments of the students in order to shape their personality. The shaping of personality is closely related to the role of religious education. Therefore, religious education has pivotal role in national education system. However, nowadays Islamic Education still faces various problems in more complex aspects, namely education dichotomy, curriculum, purposes, resources, and Islamic education management. The improvement efforts have not yet been conducted fundamentally. The efforts to update and upgrade Islamic education are often partial and not comprehensive; moreover, most systems and Islamic education institutions have not yet been managed professionally. Regarding the above problems, two approaches to overcome the weaknesses of Islamic religious education policy in schools are needed, namely the approach of policy advocacy and the approach of Islamic Religious Education curriculum development. Accordingly, Islamic Religious Education can be the basis in shaping personality of the graduates of Indonesia educational institutions in accordance with their adhered religion.